BIOCHEMICAL CHANGES IN THE LIVER OF JUVENILE AFRICAN CATFISH (Clarias gariepinus) EXPOSED TO CRUDE OIL - OROWE, A. U; OGUZIE, F. A; IKPONMWEN, E.G (Nigerian Journal of Fisheries, 2017)
This study was carried out to examine the Biochemical changes in juvenile African catfish (Clarias gariepinus) exposed to crude oil. The study was conducted using 180 juvenile catfish with mean weight of 7.993 ±0.98g and mean total length of 9.7 ± 0.72cm exposed to different concentrations (0.0%, 0.1%, 0.25%, 0.5%, 0.75% and 1.0%) of crude oil for 20 days (480 hours). The experiment was laid out as a completely randomized design and replicated thrice. Data obtained from biochemical changes, in the liver of fish were analyzed using Genstat package (version 12.1). Means were separated by the New Duncan Multiple Range Test. There were significant differences P<0.05 between enzymatic activities of the liver, Alkaline Aminotransferase (ALP) Alanine aminotransferase (ALT) and Aspartate aminotransferase (AST) in comparison with the control. There was significant elevation of ALP (36 iµ/l) and AST (88 iµ/l) in concentrations 0.10% compared to the control. Results showed no significant differences (P>0.05) between total bilirubin concentration (ranges of 0.6 mg/dl to 0.8 mg/dl) and conjugated bilirubin concentration (ranges of 0.3 mg/dl to 0.4 mg/dl). The accumulation of crude oil in the liver might cause serious pathological damage following exposure